Zirconium Modification Promotes Catalytic Activity of a Single-Site Cobalt Heterogeneous Catalyst for Propane Dehydrogenation - Zhao, Yiqing; Sohn, Hyuntae; Hu, Bo; Niklas, Jens; Poluektov, Oleg G.; Tian, Jun; Delferro, Massimiliano; Hock, Adam S. (AMER CHEMICAL SOC, 2018)
The effect of Zr modification on the catalytic activity of Co/SiO2 was investigated for nonoxidative propane dehydrogenation. Isolated Zr on SiO2 surface sites were prepared by organometallic synthesis using Zr((OBu)-Bu-t)(4) as a precursor. The resulting Zr/SiO2 support was functionalized with CO2+ ions via strong electrostatic adsorption. Spectroscopic (diffuse reflectance infrared Fourier transform spectroscopy, UV-vis, electron paramagnetic resonance) and microscopic characterization (transmission electron microscopy, scanning transition electron microscopy) results are consistent with single-site cobalt that preferentially associates with the mono-dispersed Zr at a variety of loadings and Co/Zr ratios. The oxidation state of Co in the as-prepared Co/SiO2 and Co-Zr/SiO2 was both +2 with tetrahedral and octahedral geometries, respectively. In situ X-ray absorption near edge structure and extended Xray absorption fine structure results confirmed that the oxidation state of Co remained as +2 under reaction condition for both Co/SiO2 and Co-Zr/SiO2 samples and both catalysts have tetrahedral CO2+ as the active catalyst. Despite similar Co coordination environments, the catalytic activity and selectivity was significantly improved by the Zr modification of the silica support versus Co/SiO2. This was attributed to the change in oxygen donor ability and Co-O bond strength of the SiO-Zr-O sites of Co-Zr/SiO2 compared with the SiO- ligands in Co/SiO2. These results show that tuning of the support SiO2 oxygen donation ability by use of an anchoring site (e.g., SiO-Zr-O-) can be used to alter both rate and selectivity of propane dehydrogenation with single-site heterogeneous catalysts. These results also show some preference for CO2+ active sites to associate with SiO-Zr-O- sites over SiO-.
Keywords: CHROMIUM-OXIDE CATALYSTS; ETHYLENE POLYMERIZATION; ISOBUTANE DEHYDROGENATION; OXIDATIVE DEHYDROGENATION; PROPYLENE HYDROGENATION; MESOPOROUS SILICA; SURFACE SITES; ACTIVATION; COMPLEXES; REACTIVITY